Kinetics and Mechanisms of the Chromium(III) Reactions with 2,4- and 2,5-Dihydroxybenzoic Acids in Weak Acidic Aqueous Solutions - Kimon Zavitsanos; Athinoula L. Petrou (Bioinorganic Chemistry and Applications)
The reactions of 2,4- and 2,5-dihydroxybenzoic acids (dihydroxybenzoic acid, DHBA) with chromium(III) in weak acidic aqueous solutions have been shown to take place in at least two stages. The first stage of the reactions has an observed rate constant k1(obs)=k1[DHBA]+C and the corresponding activation parameters are ΔH1(2,4)≠=49,5 kJ/mol−1, ΔS1(2,4)≠=−103,7 J mol−1 K−1, ΔH1(2,5)≠=60,3 kJ/mol−1, and ΔS1(2,5)≠=−68,0 J mol−1 K−1. These are composite activation parameters and the breaking of the strong intramolecular hydrogen bonding in the two ligands is suggested to be the first step of the (composite) first stage of the reactions. The second stage is ligand concentration independent and is thus attributed to a chelation process. The corresponding activation parameters are ΔH2(2,4)≠=45,13 kJ/mol−1, ΔS2(2,4)≠=−185,9 J mol−1 K−1, ΔH2(2,5)≠=54,55 kJ/mol−1, and ΔS2(2,5)≠=−154,8 J mol−1 K−1. The activation parameters support an associative mechanism for the second stage of the reactions. The various substitution processes are accompanied by proton release, resulting in pH decrease.